2020
DOI: 10.1111/tpj.14982
|View full text |Cite
|
Sign up to set email alerts
|

Leaflet initiation and blade expansion are separable in compound leaf development

Abstract: Compound leaves are composed of multiple separate blade units termed leaflets. In tomato (Solanum lycopersicum) compound leaves, auxin promotes both leaflet initiation and blade expansion. However, it is unclear how these two developmental processes interact. With highly variable complexity, tomato compound leaves provide an ideal system to address this question. In this study, we obtained and analyzed mutants of the WUSCHEL-RELATED HOMEOBOX (WOX) family gene SlLAM1 from tomato, whose orthologs in tobacco (Nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
(99 reference statements)
0
17
0
Order By: Relevance
“…CR-wox1-1 plants showed narrower leaves (Figures 4B and 4C) and lower LVD than M82 (Figure 4D), matching the phenotype described in wox1 mutants in other species 18,19 and tomato mutants, unfused flower (uf), and SlLAM1. [21][22][23] We noticed that these phenotypes were similar to those of the classical tomato mutant, solanifolia (sf). sf is known to have narrower leaflets and reduced vascular density, 24 and our rough mapping of the sf mutation identified a genomic location close to that known for the WOX1 locus (at the end of chromosome 3; Figure S4A).…”
Section: Articlementioning
confidence: 62%
See 3 more Smart Citations
“…CR-wox1-1 plants showed narrower leaves (Figures 4B and 4C) and lower LVD than M82 (Figure 4D), matching the phenotype described in wox1 mutants in other species 18,19 and tomato mutants, unfused flower (uf), and SlLAM1. [21][22][23] We noticed that these phenotypes were similar to those of the classical tomato mutant, solanifolia (sf). sf is known to have narrower leaflets and reduced vascular density, 24 and our rough mapping of the sf mutation identified a genomic location close to that known for the WOX1 locus (at the end of chromosome 3; Figure S4A).…”
Section: Articlementioning
confidence: 62%
“…sf single mutants with truncated WOX1 protein, such as CR-wox1-1, sf^wl, and e1862, do not have any lobes on their leaves, whereas a weaker phenotype mutant, sf, had lobed leaves (Figure 4B), suggesting that sf regulated tomato leaf development in a dosage-dependent manner. Although a previous study showed that sf was involved in floral organ growth with mutants showing severe defects in fruit development, 23 SiFT produced normal edible fruits (Figure S5E). This difference in fruit development might be related to the SF level.…”
Section: Articlementioning
confidence: 74%
See 2 more Smart Citations
“…For example, Arabidopsis CUC2 and CUC3 were dispensable for the miR‐TCP‐NGA overexpression phenotype (Alvarez et al ., 2016), while the current study shows that in tomato the increase in leaf complexity caused by downregulation of the TCP factor LA depends on intact GOB activity. Additional factors such as the WUSCHEL‐related homeobox (WOX1) and (PRESSED FLOWER) PRS also appear to have conserved roles in marginal elaboration (Lin et al ., 2013; Zhang et al ., 2014; Alvarez et al ., 2016; Guan et al ., 2017; Du et al ., 2020). It will therefore be interesting to investigate whether these are coordinated with other differentiation and patterning regulators in tomato and whether here too different species represents variations on a common theme in the precise interaction among the regulators.…”
Section: Discussionmentioning
confidence: 99%